2016
DOI: 10.4238/gmr.15028271
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effect of an A/G polymorphism in the HSP70 gene on thermotolerance in chicken

Abstract: ABSTRACT. Studying thermotolerance is important for the prevention of thermostress in chickens. This study aimed to analyze the effect of mutations in the heat shock protein 70 (HSP70) gene on chicken thermotolerance. The C.-69A>G SNP in the 5'-flanking region of the HSP70 gene was genotyped in Lingshan and White Recessive Rock (WRR) chickens. Association of this SNP with thermotolerance traits revealed it to be significantly associated with CD4+/CD8+, and potentially associated with heterophil-to-lymphocyte r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The nucleotide g.69A>G transition reported by Gan et al (2015) and Chen et al (2016) is identical to the position of g.44A>G transition in the 5′ UTR of the HSP70 gene of chicken (Morimoto et al, 1986). It is because the number reported by Gan et al (2015) and Chen et al (2016) is based on translational start and the number reported by Morimoto et al (1986) is based on transcriptional start.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The nucleotide g.69A>G transition reported by Gan et al (2015) and Chen et al (2016) is identical to the position of g.44A>G transition in the 5′ UTR of the HSP70 gene of chicken (Morimoto et al, 1986). It is because the number reported by Gan et al (2015) and Chen et al (2016) is based on translational start and the number reported by Morimoto et al (1986) is based on transcriptional start.…”
Section: Discussionmentioning
confidence: 60%
“…Research on the genetic effect of nucleotide substitution in g.69A>G, SNP (single nucleotide polymorphism) in the 5′-flanking region and its association with thermotolerance trait show that only one genotype (GG) proved useful as a marker of heat stress resistance in local Chinese chickens (Gan et al, 2015;Chen et al, 2016). The nucleotide g.69A>G transition reported by Gan et al (2015) and Chen et al (2016) is identical to the position of g.44A>G transition in the 5′ UTR of the HSP70 gene of chicken (Morimoto et al, 1986). It is because the number reported by Gan et al (2015) and Chen et al (2016) is based on translational start and the number reported by Morimoto et al (1986) is based on transcriptional start.…”
Section: Discussionmentioning
confidence: 99%
“…So that they recommended that HSP70 can be used as a marker in molecular breeding for drought/heat tolerance. Chen et al, (2016) suggested that, the GG genotype of HSP70 gene 5'-flanking region is advantageous for the prevention of thermal stress. Genotyping and allelic frequency variation of HSP70 gene by Liang et al, (2016) indicated that AA genotype has greater heat tolerance after acute heat stress in the indigenous Taiwanese chickens.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the 284 variation within individuals was high, accounting for 78.06% (Table 5). 289 Single nucleotide polymorphisms (SNPs) in the coding and non-coding regions have been 290 shown to play a critical role in regulating their function, and this has led to a better 291 understanding of the gene structure (Chen et al, 2016). To the best of our knowledge, this is the 292 first study to provide insights into the genetic polymorphisms in HSP70 among indigenous 293 chicken ecotypes in Kenya in relation to their genetic background.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the C.-69A>GSNP in 335 the 5′-flanking region of the HSP70 gene affects chickens' thermotolerance traits in white 336 recessive rock chickens exposed to thermoneutral temperatures and the GG genotype might be 337 advantageous for the prevention of heat stress. Thus, this SNP may be a potential molecular 338 marker for further genetic improvement of thermotolerance in chicken (Chen et al, 2016).…”
Section: Resultsmentioning
confidence: 99%